Interpreting immigration at museums and historic sites - Bailey, Dina A. (Interpreting history., 2018)
"Interpreting Immigration at Museums and Historic Sites includes strategies for the design, implementation, marketing and sustaining of programs that help visitors use the lens of history to address contemporary immigration issues and provides case studies, immigration program designs, audience building strategies, among others. The title considers the questions: How can museums use their collections and key stories as starting points for audience engagement around immigration past and present? How can museums move beyond the "we are a nation of immigrants" narrative - a narrative that does not resonate for all audiences? How can museums make opportunities for safe, open dialogue on immigration accessible to all stakeholders including both new immigrants and receiving communities? Interpreting Immigration includes strategies for the design, implementation, marketing and sustaining of programs that help visitors use the lens of history to address contemporary immigration issues"--